Rewriting and Rereading the XIX and XX-Century Canons Offerings for Annamaria Pagliaro - Zuccala, Brian; Grassi, Samuele (Biblioteca di Studi di Filologia Moderna, 2022)
The book takes its lead from academic Annamaria Pagliaro's experience straddling Australia and Italy over a thirty-year period. As both former colleagues and collaborators of Pagliaro, we editors intend to open a kaleidoscope of perspectives on the international research landscape in the fields of Italian and Anglophone studies, starting from Pagliaro's own contribution to the creation of relations between the two cultures in the period that saw her work transnationally as Director of the Monash University Prato Centre (2005-2008).